Corybas apoensis (Orchidaceae), a new endemic species from Mt. Apo, Philippines - Agad, Kier C.; Mallari, Archelito L.; Tandang, Danilo N.; Bustamante, Rene Alfred Anton; Salas, Daryl S. (Phytotaxa, 2026)
Corybas apoensis, a new species of tribe Acianthinae endemic to Mindanao, is described herein. Among the currently recognized species of the tribe, it most closely resembles C. viridisepalus in overall floral morphology, particularly in having upright flowers borne on a slender, cylindric, erect ovary and the flower possessing a dorsal sepal and labellum tinged with conspicuous carmine veins. Both species further share a pilose labellum. However, this notable new species is distinct by having white floral background and a dorsal sepal being densely papillate on the abaxial surface. We also provided a summarized key morphological characteristics that distinguishes our new species from the later.